Comparing the effectiveness of different approaches to raise awareness about antimicrobial resistance in farmers and veterinarians of India - Sharma, Garima; Mutua, Florence K.; Deka, Ram Pratim; Shome, R.; Bandyopadhyay, S.; Shome, B.R.; Kumar, N.G.; Grace, Delia; Dey, Tushar K.; Lindahl, Johanna F. (Frontiers Media, 2022)
Background: Antimicrobial resistance (AMR) is a global public health threat. The indiscriminate use of antibiotics in the animal health sector contributes to increasing rates of AMR and studies involving dairy farmers in India have found knowledge levels regarding antibiotics and AMR to be very low. The purpose of this study was to assess different methods to raise awareness and knowledge about AMR and antibiotic use among dairy farmers, paravets (veterinary assistants), and veterinarians.